STUDY ON THE STATUS OF BOVINE TICK INFESTATION, IN GUBA-KORICHA DISTRICT IN WEST HARARGHE ZONE, EAST - ETHIOPIA - Ababa, Henok; Negese, Tsegaye; Birru, Bekele; Nigusu, Kifle; Araya, Shibire; Gebireamlak, Wendwosen; Asres, Shimelis (International Journal of Research -GRANTHAALAYAH, 2017)
A cross-sectional study was conducted from November 2010 to April 2011 to determining the prevalence of tick infestation, to identify the common tick species in cattle and to assess the major risk factors associated with the occurrence of tick species in Guba koricha district West Hararghe zone of Oromia regional state, southeast Ethiopia. Ticks were collected by searching and half body of animals using forceps on different regions of the animals’ body. A total sample of 384 cattle, 234 were found to be infested by one or more tick species an overall prevalence of 60.9%. The most predominant isolated ticks species in this study were R. pullchelus with isolation rate of 49.4% followed A. Varigatum with isolation rate of 30.3%, H. marginatum rufipes, the third predominant with isolation rate 11.8%. However, A. gemma, H. trucatum and R. Evertsi-evertsi was the least isolate which accounts for 3.6%, 2.4% and 2.35% respectively. Age, sex and body conditions scoring were found to be important risk factors associated with tick infestation. The prevalence of tick infestation between age and sex was statistically significant (X2=32.3075, CI=0.1323358-0265075, P=0.000 andX2=5.117, CI=0.1953184-0.0061713, P=0.037) respectively. However, breed and body condition were not statistically significant (P>0.05). Hereof, Ticks are obligate, blood feeding ecto-parasites that cause severe damage to the hides and skins of domestic cattle due to this reduce the foreign exchange of the country; and transmit tick borne diseases. Therefore, effective tick control programs should be formulated and implemented at national or regional level.